Neuroserpin regulates human T cell-T cell interactions and proliferation through inhibition of tissue plasminogen activator. Issue 1 (31st October 2019) - Loef, Evert Jan; Brooks, Anna E.S.; Lorenz, Natalie; Birch, Nigel P.; Dunbar, P. Rod
Abstract: T cells play a key role in mounting an adaptive immune response. T cells are activated upon recognition of cognate Ag presented by an APC. Subsequently, T cells adhere to other activated T cells to form activation clusters, which lead to directed secretion of cytokines between communicating cells. T cell activation clusters have been implicated in regulating activation, proliferation, and memory formation in T cells. We previously reported the expression of the protease inhibitor neuroserpin by human T cells and showed that expression and intracellular localization is regulated following T cell activation. To gain a better understanding of neuroserpin in the proteolytic environment postactivation we assessed its role in human T cell clustering and proliferation. Neuroserpin knockdown increased T cell proliferation and cluster formation following T cell activation. This increased cluster formation was dependent on the proteases tissue plasminogen activator (tPA) and plasmin. Furthermore, neuroserpin knockdown or plasmin treatment of T cells increased the cleavage of annexin A2, a known plasmin target that regulates the actin cytoskeleton. Live cell imaging of activated T cells further indicated a role of the actin cytoskeleton in T cell clustering. The inhibition of actin regulators myosin ATPase and Rho-associated protein kinase signaling completely reversed the neuroserpin knockdown-induced effects. The results presented in this study reveal a novel role for neuroserpin and the proteolytic environment in the regulation of T cell activation biology.